Performance of Finger Milliet Relay Cropped with Legumes as Influenced By Establishment Times And N Levels - Purushotham, S; Shivshankar, K (Annals of Arid Zone, 2016)
Performance of finger millet as a relay crop was studied with early crops of soybean, cowpea and field beans at three N levels (0, 12.5 and 25 kg/ha). Finger millet was sown at 30 and 60 days after sowing of legumes. The yield components, N uptake any yield of finger millet were significantly influenced by different early legumes and establishment times of finger millet but not by N levels applied to the legume. Relays with soybean and cowpea gave significantly higher yields than with field beans. Early establishment of finger millet gave significantly higher yields than late establishment. The study suggests soybean and cowpea to be preferred as early crops with an early establishment of finger millet in the system, without requiring applied nitrogen.